The forgetting - Cameron, Sharon, 1970- (Scholastic Press, 2016)
Canaan is a quiet city on an idyllic world, hemmed in by high walls, but every twelve years the town breaks out in a chaos of bloody violence, after which all the people undergo the Forgetting, in which they are left without any trace of memory of themselves, their families, or their lives--but somehow seventeen-year-old Nadia has never forgotten, and she is determined to find out what causes it and how to put a stop to The Forgetting forever.